Colloidal origin of hematite in Pleistocene iron-rich sedimentary rocks from Milos Island, Greece: An analogue for Precambrian iron shuttle - Sun, Si; Klemd, Reiner; Voudouris, Panagiotis (Chemical Geology, 2025)
Banded iron formations (BIFs) are critical archives of Earth's early biogeochemical cycles, yet their genesis, especially regarding the origin of hematite and associated Fe transport mechanisms, remains intensely debated. The scarcity of unmetamorphosed Phanerozoic analogues has constrained a comprehensive understanding of BIF formation. Here, we investigate Pleistocene iron-rich sedimentary rocks from the Cape Vani sedimentary basin, Milos Island, Greece, to elucidate Fe transport processes in ancient oceans. High-resolution petrographic mineralogical, and spectroscopic analyses reveal that Fe is predominantly hosted in hematite nanoparticles (ca. 0.1–0.75 μm), which often form framboidal and irregular aggregates. Mössbauer spectroscopy indicates that the hematite has magnetic hyperfine fields (46.75–50.73 T) characteristic of medium to poor crystallinity. Raman spectra further exhibit a prominent band shift ca. 650 cm−1, a feature diagnostic of nanocrystalline hematite. Carbonaceous material is spatially associated with the aggregates but is absent from individual nanoparticles. The uniform sizes and morphology of the hematite particles suggest that the majority of Fe was transported as colloids. This implies a possible allochthonous origin and ex situ Fe-oxidation, since colloids can be transported over long distances. The aggregation and subsequent deposition of these colloids were likely facilitated by high concentrations of dissolved Si and interactions with carbonaceous materials. The prevalence of colloidally-derived hematite at Milos highlights colloidal transport as a potentially significant mechanism for iron distribution in past oceans. Consequently, the presence of hematite in ancient sediments like BIFs does not necessarily imply in situ Fe-oxidation or associated microbial processes. The established model for a colloidal iron shuttle capable of transporting iron across oceanic basins offers a new perspective for interpreting the genesis of BIFs and a refined understanding on the early Earth's biogeochemical cycles.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Banded iron formation; Colloidal transport; Ex situoxidation; Hematite nanoparticles; iron shuttle